SOLD FLAT AGREEMENT OF SONG COPYRIGHT AS A TRANSFER OF ECONOMIC RIGHTS - Huliselan, Rastra Samara (jfpublisher, 2025)
In the music industry context, before Law Number 28 of 2014 concerning Copyright was enacted, the bargaining position of Creators and Performers was very weak when dealing with Phonogram Producers or Recording Companies, which generally possessed greater economic power. At that time, Creators and Performers were generally not in good economic condition, leading Phonogram Producers or copyright buyers to abuse the situation (misbruik van omstandigheden) by utilizing their stronger bargaining position to impose agreement contents unconditionally. The research questions are: how does the basic concept of sold flat agreements apply to song copyrights regarding economic rights transfer, and how is the freedom of contract principle applied in sold flat agreements? This research employs normative legal research methods by examining literature studies and relevant laws. The results show that in practice, collaboration between song creators and sound recording producers involves agreement letters generally prepared by producers. Song creators only sign them after being given opportunities to study the agreement concepts beforehand. The preparation is solely for practical purposes. In practice, song creators' bargaining position is often lower than sound recording producers. Based on Article 18 of the Copyright Law, sold flat agreements must return copyright to creators after 25 years. However, during this period, creators only enjoy minimal benefits from their creations. Therefore, the state must strictly supervise contracts in sold flat agreements, particularly regarding standard clauses offered by buyers, and should stipulate that song creators can receive state-regulated royalties even after sold flat contract execution.